Eksistensi Tuhan Menurut Immanuel Kant: Jalan Moral Menuju Tuhan - Simon Petrus L. Tjahjadi (Jurnal Orientasi Baru, 2009)
What is the relation between ethics, happiness and God? Immanuel Kant hasa web of arguments explaining their intertwined relations in his well knownworks. This body of arguments laid an intellectual bridge between philosophyand theology. God is understood as 1) a moral unit who ensures the absoluteautonomy of human conscience, as well as 2) guarantee the foundation ofmorality or the ultimate meaning of morality. Yet, this kind of God isnamed by Kant as postulate, meaning that the existence is to be acceptedunconditionally or needless to prove it otherwise. In Fakta der Vernunft, KpV,A 289, Kant named it as the fact of reason. This means that for humanbeings, ethics, happiness and God are to be accepted beyond any doubt (asin the case of a fact). On the other hand, they should not be considered asan empirical constancy, as to be able to be finger-pointed, however as a resultof a conclusion of a work of human practical reason along with his or hermoral effort.